Urban rail network connectivity in locating transfer stations: a case study of Tehran urban railway - Ghiasi, Vahed; Omar, Husaini; Md Yusoff, Zainuddin; Ghiasi, Samad; Kim Huat, Bujang; Muniandy, Ratnasamy; Baharvand, Moharam; Hosaini, Seyed Ghavamoddin; Souri, Morteza; Ghosni, Nassimsadat; Noushini, Amin; Afshar, Mohammad Amin; et al. (Academic Journals, 2011)
Public transport connectivity is defined as the ability to provide service to a maximum of trips through the optimal integration of lines, schedules, fare systems, information systems and modal transport facilities. Main interchange and big transfer stations are important factors in network connectivity. One of the objectives of this paper is defining the various types of interchange and transfer stations. Specifying the differences between these two is another aim of this paper. Finally, the process of locating interchange and transfer stations is discussed as the most important factor in network connectivity. Case study of Tehran urban rail network and the location of interchange and transfer stations is presented as an example of rail network connectivity.